2015
DOI: 10.1002/ange.201506430
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Artificial Cholesteryl Crown Ether K+‐Channels

Abstract: The bacterial KcsA channel conducts K + cations at high rates while excluding Na + cations.H erein, we report an artificial ion-channel formed by H-bonded stacks of crownethers,w here K + cation conduction is highly preferred to Na + cations.T he macrocycles aligned along the central pore surround the K + cations in as imilar manner to the water around the hydrated cation, compensating for the energetic cost of their dehydration. In contrast, the Na + cation does not fit the macrocyclic binding sites,s oi ts d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 55 publications
2
19
0
Order By: Relevance
“…Energy barriers resulting from ion dehydration at the pore mouth have been adopted to explain selectivity between similar ions in subnanometer pores ( 9 ). Hence, it was concluded that to facilitate the permeation of specific ions, the ion-pore attraction near the pore entrance should be increased to reduce the energy barrier for the ion to enter the pore ( 21 , 56 , 57 ). However, according to our simulations and experimental results, the overall energy for ion permeation through relatively long subnanometer pores is governed by the intrapore diffusion, rather than partitioning at the pore entrance, due to the strong ion-pore wall interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Energy barriers resulting from ion dehydration at the pore mouth have been adopted to explain selectivity between similar ions in subnanometer pores ( 9 ). Hence, it was concluded that to facilitate the permeation of specific ions, the ion-pore attraction near the pore entrance should be increased to reduce the energy barrier for the ion to enter the pore ( 21 , 56 , 57 ). However, according to our simulations and experimental results, the overall energy for ion permeation through relatively long subnanometer pores is governed by the intrapore diffusion, rather than partitioning at the pore entrance, due to the strong ion-pore wall interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, biological channels can differentiate between ions of the same charge, such as potassium and sodium 3 . One can envision, however, that the ability to impart chemical selectivity at specific locations along the nanopore could also be incorporated into this platform, as recently shown through crown-ether functionalization of nanopores 37 , and crown-ether channels [38][39][40][41] . Such ion selective channels would enable a selective response of the amplifying circuits to specific ions.…”
Section: Discussionmentioning
confidence: 99%
“…A conventional ion-relay mechanism for ion transport requires three or more relay stations to fully span the hydrophobic membrane region, with at least one station residing around the center of the membrane where ions experience the highest energetic penalty. 18,[30][31][32][33][34][35][36][37] During the ion-relay process, where the preceding station captures and relays the ion to the next station, all stations do not move significantly. We envisioned that the number of relay stations could be reduced to two if they are customized to be capable of swinging along the membrane axis back and forth between the membrane's hydrophilic region and its center.…”
Section: Initial Statementioning
confidence: 99%